Oral health status of patients seeking therapeutic and rehabilitative care for cleft lip and cleft palate at specialty hospitals in vadodara - Ricky Pal Singh; C G Ajithkrishnan; Thanveer Kalantharkath; Amrita Pawar; Harshal Bafna; Pulkit Kalyan; Avnish Singh (Wolters Kluwer Medknow Publications, 2019)
Aim: To assess the oral health status of the patients seeking therapeutic and rehabilitative care for cleft lip and cleft palate at specialty hospitals of Vadodara district, Gujarat. Objectives: Record the Oral Health Status of the patients undergoing therapeutic and rehabilitative care for cleft lip and cleft palate or both by using WHO 2004 methodology. Material and Methods: A descriptive cross sectional survey was conducted at the three specialty centers of Vadodara district for a period of six months. All the subjects with cleft lip and cleft palate reporting to the OPD of these Centre were examined. Total 52 subjects reporting to these Centre were included and the data was recorded according to the Multi-centric Oral health survey-2004. The data related to oral health status was recorded, compiled, tabulated and was subjected to statistical analysis using SPSS package. Results: Among the 52 subjects examined, 32 were males and 20 were females. All the subjects had dental caries, gingival bleeding was seen in 71.1% of subjects and pockets were seen in 67.30%. Loss of attachment was seen in 96.65% of the subjects. Mean caries experience was more in males 5.78±1.18 as compared to females, whereas gingival bleeding was more in females. 19.23% of the subjects had ulcerations, 50% had abnormality of the upper lips and 15.38% had very mild fluorosis. Conclusion: In general, cleft lip and/or palate subjects exhibited poor oral health status with a higher level of caries experience and poor periodontal condition.